A‐posteriori‐derived dietary patterns and cognitive function in the SUN project: Prevention (nonpharmacological) / Nutrition. (7th December 2020) - Muñoz‐García, Mariana I; Martinez‐Gonzalez, Miguel Angel; Razquin, Cristina; Fernández‐Matarrubia, Marta; Guillen‐Grima, Francisco; Toledo, Estefanía
Abstract: Background: Dementia affected an estimated 44 million persons in 2016 and it is projected to affect 132 million by 2050. Drugs to cure or delay the progression of the disease are not available and are proving difficult to develop. Thus, prevention of cognitive function decline is extremely relevant. Diet is a key and pertinent target for primary prevention, but firm recommendations for dementia prevention are not available yet. Our aim was to address the association between empirically derived dietary patterns (DP) and changes in Spanish Telephone Interview for Cognitive Status (STICS‐m) scores over 6 years in a Mediterranean cohort. Method: A total of 803 participants from the 'Seguimiento Universidad de Navarra' (SUN) Project sub‐study of cognitive function were analyzed using principal component analysis to derive DP. The derived DP were associated with change in STICS‐m scores over 6 years, through adjusted multiple linear regression models. Result: Two main DP were identified. The first resembled a Western diet (WDP)— high in sugar, fat, processed foods and red meat— and the second one a Mediterranean diet (MDP)— high in vegetable, fruit, nuts, fish and olive oil (table 1). Baseline characteristics of participants are shown in table 2. Highest adherence to the WDP (tertile 3 vs tertile 1) was associated with a non‐significant decrease in STICS‐m after 6 years of ‐0.65 points (95% CI ‐1.36, 0.06, p‐value=0.07) (figure 1). On the other hand, results for the MDP were showed a 0.73 point increase in STICS‐m after 6 years (95% CI 0.18, 1.27, p‐value=0.008), comparing tertile 3 vs tertile 1 (figure 2). Conclusion: A healthy, prudent, Mediterranean‐like DP was associated with less decline in cognitive function and, thus, could help to lower dementia incidence. Western‐type diets could be associated with a faster decline in cognitive performance and higher dementia incidence. Our results are compatible with previous studies in other populations and can have an impact in future public health recommendations to decrease the risk of developing dementia.